Improving fried chicken quality through the introduction of enzyme technology - Cahyo Indarto; Raden Arief Firmansyah; Wahyu Prihanta (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Undirect efforts have been made by Gadungan village's government at Puncu sub-district, Kediri regency, to surpass the stunting level through entrepreneurship. Its purpose is to elevate the financial level of the community. The form of enterprise development is fried chicken production managed by Pokwan “ASKARA.” However, the quality of fried chicken is low, and it is difficult to compete with other competitors in the same business type. The event about introducing an enzyme technology was held to elevate the quality of fried chicken. Besides increasing product quality, enzyme technology was safe for human beings. This event was held in three main steps: introduction of enzyme technology, practice making fried chicken products using enzyme technology and evaluation event. The evaluation process used the Kirkpatrick model at three levels: reaction, learning, and behavior level. The result showed that evaluation of all levels obtained more than 4.00, and more than 80 percent of respondents strongly agreed and agreed with each item in the questionnaire. The results also showed that this event succeeded in motivating the participant to use enzyme technology for fried chicken production, which produces crispy and crunchy fried chicken that is also safe.